Barriers and facilitators to feeling safe for inpatients: a model based on a qualitative meta-synthesis - Yan, Lupei; Liu, Li; Wang, Fang; Zhao, Fanyu; Hu, Xiuying (Frontiers in Public Health, 2024)
Objectives To review and synthesize qualitative research exploring patients’ safe experience and construct a model to present barriers and facilitators to feeling safe for inpatients. Design A qualitative met-synthesis. Methods We conducted a systematic electronic search of articles published in English with no date limitation across five databases (Ovid MEDLINE, EMBASE, Web of Science, CINAIL via EBSCO, and PsyINFO) in May 2023. Qualitative research focused on the safe experiences of inpatients was considered. Systematic searches yielded 8,132 studies, of which 16 articles were included. Two reviewers independently extracted and analyzed data. Qualitative meta-synthesis was performed through line-by-line coding of original texts, organizing codes into descriptive themes, and generating analytical themes. Results We identified four themes and 11 sub-themes. Across the four themes, control included a barrier (Uncertainty) and two facilitators (Patient participation and safe care); responsible included three facilitators (Confidence in the profession, care for, and responsive); dignity included two barriers (Privacy and Neglect); stability included a barrier (Potential risk), and two facilitators (Harmonious and safe culture). We constructed a model to present the logical connection between these themes and related barriers and facilitators. Conclusion Feeling safe for inpatients is a complex perception, including four themes: control, responsible, dignity, and stability. Surrounding four themes and related barriers and facilitators, we outline principles for creating a safe environment and present strategies for improving patients’ hospitalization experience and ensuring patient safety. Clinical relevance This review provides valuable insight into the clinical practice and health policy and helps medical staff to identify and overcome the potential barriers to implementing interventions in safe care. In addition, the model comprehensively describes the nature and dimensions of feeling safe, informing high-quality care service and related research. Systematic review registration Identifier, CRD42023435489.